How to control single-molecule rotation - Grant J. Simpson (Nature Portfolio, 2019)
The orientation of a molecule on a surface affects many processes, so the ability to control single-molecule rotation could be powerful. Here, the authors use the electric field from a scanning tunneling microscope tip to precisely induce unidirectional rotation of a polar molecule, allowing visualization of the molecule’s internal dipole moment.